Global Research Trends on Oral Diseases Amid the Double Burden of Diabetes and Tuberculosis: A Bibliometric Analysis - Dian Yosi Arinawati; Seshy Tinartayu; Maria Ulfa; Shaista Afroz (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Diabetes Mellitus (DM) and Tuberculosis (TB) present significant health challenges in low- and middle-income countries (LMICs). DM increases the risk of active TB by 2 to 4 times due to weakened immunity, and the number of adults with DM is projected to rise from 463 million in 2019 to 700 million by 2045, with 80% in LMICs where TB is common. This co-occurrence complicates treatment, as TB can worsen glycemic control and poorly managed DM affects immunity. Although DM is linked to periodontitis and TB can cause ulcers, the oral health implications remain underexplored. The objective was to identify research themes and collaboration networks for improving oral healthcare among patients with tuberculosis and diabetes mellitus comorbidities, who also have oral diseases. The broader aim is to improve oral healthcare and reduce the burden of chronic diseases in these populations. Methods: A qualitative literature review was conducted using peer-reviewed journals from 2018 to 2024 in the Scopus database. The search employed the keywords “oral AND diseases AND tuberculosis AND diabetes AND mellitus,” focusing solely on English documents in various medical fields. Data collection in March 2025 aimed to minimize bias. Descriptive and bibliometric analyses were performed using RStudio and VOSviewer to examine trends and correlations among oral diseases, tuberculosis, and diabetes mellitus. This analysis is conducted through cocitation and keyword patterns. Results: A review of 146 publications from 2018 to 2024 found that only six (4.1%) focused on oral health in tuberculosis and diabetes mellitus (TB-DM). The average annual growth rate of publications was 8.89%. Four main themes emerged: (1) complications of diabetes mellitus, (2) tuberculosis examination and treatment, (3) prevalence and risk factors of type 2 diabetes, and (4) TB-DM interactions. India, the USA, and Japan were the leading contributors. The top keywords were "diabetes mellitus" (900), "tuberculosis" (735), and "non-insulin-dependent diabetes mellitus" (431). Conclusion: Future research should adopt an interdisciplinary approach to investigate the effect of systemic inflammation and medication interactions on oral health in DM-TB populations. Longitudinal studies are necessary to assess the impact of oral interventions on glycemic control and treatment success for TB. Collaboration among dental and medical professionals is essential for delivering integrated care models that prioritize both oral and systemic health.